Performance comparison of wavelet thresholding techniques on weak ECG signal denoising - Üstünda?, Mehmet; Şengür, Abdulkadir; Gökbulut, Muammer; Ata, Fikret (My University, 2013)
The Electrocardiogram (ECG) signal is a biological non-stationary signal which contains important information about rhythms of heart. ECG signals can be buried by various types of noise. These types can be electrode movement, strong electromagnetic effect and muscle noise. Noisy ECG signal has been denoised using signal processing. This paper presents a weak ECG signal denoising method based on interval-dependent thresholds of wavelet analysis. Several experiments were conducted to show the effectiveness of the interval-dependent thresholding method and compared the results with the soft and hard wavelet thresholding methods for denoising. The results are evaluated by calculating the root mean square error and the correlation coefficient.
Porównanie dzia?ania metod progowania falkowego w odszumianiu sygna?ów EKG
Keywords: ECG signal; Interval-dependent thresholding; Wavelet denoising